Micro graphite-patterned diamond sensors: Towards the simultaneous in vitro detection of molecular release and action potentials generation from excitable cells. (November 2019) - Tomagra, Giulia; Aprà, Pietro; Battiato, Alfio; Collà Ruvolo, Cecilia; Pasquarelli, Alberto; Marcantoni, Andrea; Carbone, Emilio; Carabelli, Valentina; Olivero, Paolo; Picollo, Federico
Abstract: In neuroscience, a deep understanding of communication mechanisms at the cellular level is of paramount importance, since their dysfunction determines the onset of several diseases. The development of innovative sensors devoted to the investigation of both chemical and electrical signals it is therefore essential to improve the outcome of standard trials and to define novel methodologies. Here we report on the fabrication and the characterization of multi-functional micrographite patterned diamond multi-electrode arrays. These sensors are obtained by means of a three-dimensional patterning process of single-crystal diamond substrates by means of MeV ion-beam-based lithography, which allows the direct fabrication of graphitic micro-channels embedded within the bulk of the electrically insulating diamond matrix. Proof-of-concept in vitro experiments on cultured neurons and cardiac tissue were performed, in which quantal secretory events were amperometrically recorded from dopaminergic neurons, while potentiometric measurements of action potential generation were collected from both hippocampal neuronal networks and intact sinoatrial nodes. These achievements represent the demonstration of the applicability of an all-carbon hybrid graphite/diamond device for the multi parametric detection of chemical and electrical signals, thus representing a fundamental step for the simultaneous in vitro measurement of the two types of signals from the same biological sample. Graphical abstract: Image 1